Management of Acute Diarrhea: A Study on Community Pharmacists’ Attitudes in Iran - Vaseghi, Golnaz; Eshraghi, Azadeh; Eslami, Neda; Masjedi, Moein; Mehrpooya, Maryam; Eshraghi, Nazanin (Reviews on Recent Clinical Trials, 2015)
Diarrhea disease is one of the most important problem which leads to mortality and morbidity in under developing country. Pharmacists play an important role in providing health services to local communities for this common health issues. The purpose of our study was to assess diarrhea related attitude and knowledge of pharmacist in Iran. This study has been performed in Iranian Pharmacist Association congress in2012. This is conducted as a questionnaire base, in 100 randomly Persian pharmacists, consists of questions about demographic data of pharmacists such as age, sex, college, year of study, attitude and knowledge of pharmacists on management of acute diarrhea. Pharmacists believed that it was important to ask about the age of patients (98%), initiation (98%) and frequency (95%) of diarrhea, blood (90%) in diarrhea, other symptoms such as fever or pain (95%) as well as recent foods consumption (91%). However there was a significance differences between male and female pharmacist about their diarrhea knowledge. Among pharmacists, 75% asked about the recent travel and 63% asked about other affected family members .Most pharmacists (78) dispensed ORS for the pediatric acute diarrhea. However, some believed in recommending ORS+ antimotility drugs (9%), ORS+ antismaspolitic (11%) and ORS + antibiotics (2 %). Although iranian pharmacist were in a good attitude however the rule of periodic studies should highlighted.
Keywords: pharmacist